2015
DOI: 10.1016/j.rinp.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic flow with thermal conductivity of H 2 O + Cu nanofluid and entropy generation

Abstract: a b s t r a c tIn this article, it is opted to investigate the effects of entropy and induced magnetic field for the peristaltic flow of copper water fluid in the asymmetric horizontal channel , the mathematical formulation is presented, the resulting equations are solved exactly. The obtained expressions for pressure gradient , pressure rise, temperature, axial magnetic field, current density, velocity phenomenon entropy generation number and Bejan number are described through graphs for various pertinent par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…For the velocity components U along the X and V along the Y− directions in the fixed frame, one can write V as: The law of conservation of mass, momentum, and energy can be written as [16,37,43,44]: The law of conservation of mass, momentum, and energy can be written as [16,37,43,44]:…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the velocity components U along the X and V along the Y− directions in the fixed frame, one can write V as: The law of conservation of mass, momentum, and energy can be written as [16,37,43,44]: The law of conservation of mass, momentum, and energy can be written as [16,37,43,44]:…”
Section: Problem Formulationmentioning
confidence: 99%
“…They analyzed that peristalsis is a great entropy generator process, due essentially to dynamic irreversibility. Some more interesting studies in this direction can be consulted in References [36][37][38][39]. Existing literature witnesses that no attention is focused so far on the study of entropy generation on mixed convection [9,[40][41][42][43][44] peristaltic flow in the presence of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the entropy generation approaches zero near to the free stream region. Akbar et al [15] presented the effect of the entropy and the magnetic field on the peristaltic flow of the copper water fluid in an asymmetric horizontal channel. They showed that the entropy generation number increases with the Brinkman number.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Abolbashari et al [24] have investigated analytically the fluid flow with heat and mass transfer and entropy generation for the steady laminar non-Newtonian nanofluid induced by stretching sheet in the presence of velocity slip and convective surface boundary condition. Few more attempts are taken into account of entropy generation on nanofluid with stretching surface with different geometry [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%